Relevance of Problem Based Learning based on Science Education for Sustainability Development towards Problem Solving Ability - Pratiwi, Reni Indah Ayu; Fadly, Wirawan; Faizah, Ulinnuha Nur; Al Ethari, Rawaa Yasir Mahdi (UIN Fatmawati Sukarno Bengkulu, 2023)
One of the skills that students must master is problem solving abilities, in which students will learn tosolve problems in their surroundings. This study aims to determine the effectiveness of the PBL (ProblemBased Learning) model integrated with the Science Education for Sustainability Development (SESD)approach to students' problem solving abilities. The use of the SESD-integrated PBL model in problemsolving ability is something new that has never been done. The study used a quasi-experimental designquantitative method with a pretest-posttest design. The research sample was 24 students of grade 8thjunior high school as an experimental class that applied the integrated PBL model with SESD and 24students of grade 8th junior high school as the control class that applied the non-PBL model integratedwith SESD. Data collection techniques used observation sheets, tests, and questionnaires, which wereanalyzed using descriptive and inferential statistics. The results of the two-tailed t-test yielded a P-Value of0.001, where if the P-Value < α = 5% (0.05), then H0 was rejected. So it shows that there is a significantdifference in problem solving ability between the experimental class and the control class. The results ofthe one-tailed t-test that has been carried out produce a P-Value of 0.001 so that H0 is accepted. Theresults of the one-tailed t-test also show an estimate for a difference of 13.85. Therefore, the test decisioncan be stated that the problem solving abilities of students in the experimental class are better than thosein the control class. The ANCOVA test shows that the value of Sig. of 0.010 < α (0.05) shows that thePBL model integrated with SESD is considered effective for problem solving abilities. So it can beconcluded that students' problem solving abilities using integrated PBL models with SESD are moreeffective than students' problem solving abilities using non-PBL models integrated with SESD